Worker's unemployment protection systems in the OAS countries - Islas, Gonzalo (ILO LimaPE, 2002)
Analyzes the main theoretical aspects as well as the current discussion, regarding, under which grounds unemployment insurance should be implemented. Shows how this discussion relates to the OAS countries